Fracture of the Elongated Styloid Process by Hanging - Bork, Turgay; Batbaş, Muhammet; Vicdanlı, Nazif Harun; Türkoglu, Abdurrahım (My University, 2022)
It is a routine protocol to examine the soft tissues, cartilage and bone tissues of the neck during post-mortem examinations performed in the cases of hanging-related deaths. Fractures of the hyoid bone and thyroid cartilage, as well as bleeding and ecchymoses around the first fracture are practically of great importance in establishing the case as live hanging. The styloid process is a thin bone at the base of the skull that extends downward, medially, and anteriorly from the temporal bone. Elongated variations of styloid process are encountered in society. In literature, there are no reported cases of elongated styloid process fractures due to hanging. In hanging-related deaths, along with hyoid bone and thyroid cartilage tissues, styloid process should also be evaluated for fractures.
Keywords: Autopsy; styloid proces; hanging.